GAMBARAN TANDA INFEKSI LOKAL LUKA POST SIRKUMSISI PADA USIA DEWASA DI KLINIK RATANCA MALANG - Ardiyani, Vita Maryah; Sutriningsih, Ani; Supriyadi, Supriyadi (Universitas Tribhuwana Tunggadewi, 2020)
Khitan or sirkumsisi is the act of cutting or completely wash out most cover foreskin of the penis based health reasons, culture or religious belief . The act of sirkumsisi going to leave scar tissue that need attention the handling and so does not carry infection. The Research aimed to identify marks infection of local injuries post sirkumsisi among those persons sirkumsisi in adult at ratanca malang clinic .The research uses observational descriptive design .The population all participants who register as many as 20 sirkumsisi operation of a person taken in total the sampling method .Variable free consisting of pain , reddish , heat , swollen , and the existence of the pus to wounds post sirkumsisi 3rd day .Data analyzed a sort of descriptive set .The results of the study or the sign of a local infection consisting of a reddish (95%) , pain (95%) , heat (85%), swollen (85%), and the absence of pus (80%) in about wound post sirkumsisi . Further Research said must be implemented to observe sirkumsisi wound among respondents adults in a longer period of time and measuring factors influencing the healing of injured sirkumsi.